An Analysis of Inservice Mathematics Teachers' Reading of Curriculum Materials: Focused on Conditional Probability - Nayoung Ku; Byungjoo Tak; Inyong Choi; Hyun-Young Kang (Korea Society of Educational Studies in Mathematics, 2020)
In this study, 218 highschool mathematics teachers were surveyed to identify their perceptions and reading of curriculum materials. As a result, the majority of teachers emphasized the agency of teachers in enacting the curriculum and regarded conceptual understanding as crucial in teaching conditional probability. Nevertheless, the analysis of reading of the 2015 revised mathematics curriculum showed the lowest frequency of responses using the teachers' knowledge and experience. Among the major changes in the 2015 revised mathematics curriculum related conditional probability, teachers mentioned in the order of attitude and practice, information processing, reducing the burden of learning, improving evaluation methods, and reasoning. When teachers mentioned reasoning, they were more likely to evaluate or interpret the curriculum materials using their knowledge and experience. But most of teachers stated that the other changes as particular features were included. Thus, opportunities must be provided to improve teachers' professional development based on the concrete methods that can enact the intention of the 2015 revised mathematics curriculum.